Surgical anatomy and histology of the levator palpebrae superioris muscle for blepharoptosis correction - Djordjević, Boban Sava; Novaković, Marijan Jovan; Milisavljević, Milan Miodrag; Milićević, Saša Dragiša; Maliković, Aleksandar Božidar (Vojnosanitetski pregled, 2017)
Background/Aim. The detailed knowledge of the architecture of the upper eyelid is very important in numerous upper eyelid corrective surgeries. The article deals with the detailed anatomy of the major components of the upper lid, which are commonly seen in surgical practice. Methods. This study was conducted on 19 human cadavers (12 adults and 7 infants) without pathologic changes in the orbital region and eyelids. Anatomic microdissection of the contents of the orbita was performed bilaterally on 12 orbits from 6 unfixed cadavers (3 male and 3 female). Micromorphologic investigations of the orbital tissue were performed on 8 en bloc excised and formalin-fixed orbits of infant cadavers. Specimens were fixed according to the Duvernoy method. An intra-arterial injection of 5% mixture of melt formalin and black ink was administered into the carotid arterial system. Using routine fixation, decalcination, dehydration, illumination, impregnation and molding procedures in paraplast, specimens were prepared for cross-sections. Results. The measurement of the muscle length and diameter in situ in 6 nonfixed cadavers (12 orbits) showed an average length of the levator palpbrae superioris (LPS) muscle body of the 42.0 ± 1.41 mm on the right, and 40.3 ± 1.63 mm on the left side. In all the cases, the LPS had blood supply from 4 different arterial systems: the lacrimal, supratrochlear, and supraorbital artery and muscle branches of the ophthalmic artery. The LPS muscle in all the specimens was supplied by the superior medial branch of the oculomotor nerve. The connective tissue associated with the LPS muscle contains two transverse ligaments: the superior (Whitnall’s) and intermuscular transverse ligaments (ITL). The orbital septum in all the specimens originated from the arcus marginalis of the frontal bone, and consisted of two layers – the superficial and the inner layer. In addition, a detailed histological analysis revealed that the upper eyelid’s crease was formed by the conjoined fascia including the fascia of the orbicularis muscle, the superficial layer of the orbital septum, and the aponeurosis of the LPS muscle, as well as the pretarsal fascia. Conclusion. The conducted study provided a valuable morphological basis for biomechanical and clinical considerations regarding blepharoptosis surgery.